2005
DOI: 10.1002/cbic.200500203
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Catanionic Assemblies: In vitro Anti‐HIV Activity of Phosphorus‐Containing Dendrimers Bearing Galβ1cer Analogues

Abstract: Two series of water-soluble dendritic catanionic assemblies, acting as multisite analogues of galactosylceramide (Galbeta1cer), have been prepared with the goal of blocking HIV infection prior to the entry of the virus into human cells. Trifunctional and hexafunctional cinnamic acid-terminated dendrimers have been synthesized from phosphorus-containing dendrimers bearing aldehyde end groups. A classical acid-base reaction performed in water between acid-terminated dendrimers and stoichiometric amounts of N-hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 43 publications
0
73
0
Order By: Relevance
“…This dendrimer was tested for the activation of monocytes [38], but also for obtaining catanionic (saline, containing both cationic and anionic centers) multivalent analogs of GalCer (galactosylceramide) by interaction of this dendrimer with N-hexadecylaminolactitol moieties [121]. These types of catanionic systems proved to be good HIV-1 inhibitors [122]. Addition of phosphonate HPO 3 Me 3 can be carried out also on imine terminal functions, affording in this case three types of terminal functions, phosphonates, secondary amines, and alkyl groups ( Figure 18) [117].…”
Section: Dendritic Structures With Two Types Of Functions On Each Termentioning
confidence: 99%
“…This dendrimer was tested for the activation of monocytes [38], but also for obtaining catanionic (saline, containing both cationic and anionic centers) multivalent analogs of GalCer (galactosylceramide) by interaction of this dendrimer with N-hexadecylaminolactitol moieties [121]. These types of catanionic systems proved to be good HIV-1 inhibitors [122]. Addition of phosphonate HPO 3 Me 3 can be carried out also on imine terminal functions, affording in this case three types of terminal functions, phosphonates, secondary amines, and alkyl groups ( Figure 18) [117].…”
Section: Dendritic Structures With Two Types Of Functions On Each Termentioning
confidence: 99%
“…Other types of GalCer-based dendrimers having polyglycerol (PG) core (Morales-Serna et al, 2010) and phosphonic acid (PA) core (Perez-Anes et al, 2010) were studied, and shown to inhibit cell-based HIV assays. However, one difference between the GalCer-PG, GalCer-PA and GalCer-PPI based dendrimers is that the earlier two dendrimer types have high cytotoxic effects as compared to the latter, though they have binding affinities in the sub micromolar (μM) range (Blanzat et al, 2005;Perez-Anes et al, 2010). The other types of PPI core based dendrimers include terminating glycosphingolipid derived sugar head groups, 3'-siallyactose (GM 3 ) or globotriose (Gb 3 ) (Borges et al, 2010).…”
Section: Anti-viral Activitymentioning
confidence: 99%
“…Antiviral assays confirmed the crucial roles played both by multivalency effects and lipophilicity on the biological activity of Galβ1cer analogues. Furthermore the shape of the dendrimers is also a very important criterion, since the second generation built from the trifunctional core and the first generation built from the hexafunctional core, both decorated with 12 hexadecylaminolactitol moieties, exhibit very different IC50 values of 1.1 and 0.12 mM, respectively (Blanzat et al, 2005).…”
Section: Phosphorhydrazone Dendrimers En-ded By Carboxylate Groupsmentioning
confidence: 99%